A TMF crack propagation model considering time dependency and load sequence effects. (1st October 2020) - Rupp, Michael; Dhondt, Guido; Becker, Martin; Fischersworring-Bunk, Andreas; Rohr, Antje; Brendel, Thomas; Hackenberg, Hans-Peter
Abstract: Due to increasing temperatures and mechanical loads in aero engine turbine components, the prediction of thermomechanical life requires accurate crack propagation calculations under thermomechanical Fatigue (TMF) conditions. Based on a linear elastic crack propagation model which considers pure cyclic crack propagation behavior only, a crack propagation model was developed to accurately predict TMF crack propagation life. It is considering short crack behavior by an El Haddad approach, time dependent effects by a combined creep and oxidation model, as well as cyclic and static time dependent load sequence effects described by a modified Willenborg model. Furthermore, an approach was developed to calculate the time dependent threshold behavior. The model can be applied to arbitrary mission profiles. A total of 29 parameters are required to describe all considered effects. As an example, these were calibrated by isothermal cyclic crack propagation, threshold and creep crack propagation tests on Inconel 718 at three temperatures. TMF crack propagation tests were carried out to validate the capability of the model. It is shown that the calculated crack propagation rates and thresholds, and consequently the predicted crack propagation life, match the measured data very well for isothermal as well as for TMF conditions.